A numerical investigation into the impact of icing on the aerodynamic performance of aerofoils - Bhatia, Dinesh; Wahaibi, Al Yaqadan Shaaban al (2020)
Aircraft wings and wind turbine blades are often subjected to harsh and cold climatic conditions. Icing is often observed on wing and blade surfaces in these cold climatic conditions. Wind turbine blades, in particular, are severely impacted by ice accretion which greatly hampers their performance and energy generation efficiency. Ice-accretion patterns are observed to vary with changes in temperature. As the temperature changes, the thickness of the ice accretion, the shape and location of ice-accretion vary greatly. In this paper, three different ice accretion patterns and their impact on the aerofoil efficiency have been investigated using the SST